2019
DOI: 10.1017/s1049023x19004394
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Prehospital On-Scene Time in an Australian Emergency Retrieval Service

Abstract: Introduction:Prehospital physicians balance the need to stabilize patients prior to transport, minimizing the delay to transport patients to the appropriate level of care. Literature has focused on which interventions should be performed in the prehospital environment, with airway management, specifically prehospital intubation (PHI), being a commonly discussed topic. However, few studies have sought additional factors which influence scene time or quantify the impact of mission characteristics or therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…Although we look for explanations in Saudi EMS setting, the gender differences are not confined to our study. Our findings are in line with several studies from other countries which often found that women had a longer median or average OST compared with men 12 28 29 31 33 34. None of these studies investigated the impact of different sociocultural factors on spent time at the scene for patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although we look for explanations in Saudi EMS setting, the gender differences are not confined to our study. Our findings are in line with several studies from other countries which often found that women had a longer median or average OST compared with men 12 28 29 31 33 34. None of these studies investigated the impact of different sociocultural factors on spent time at the scene for patients.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, although the median OST for elderly people was longer than adults and children, the intergender variation in the OST duration for elderly people was negligible compared with adults and children. A plausible explanation for prolonged OST for the elderly might be attributed to the difficulty in communication with them about the severity of their medical conditions and that more time was required to stabilise them 29. A Swedish study found that an increase in age is directly proportional to an increase in OST 30.…”
Section: Discussionmentioning
confidence: 99%
“…4 min, 95% CI 26.1-42.8)(37). These patients were however not in cardiac arrest, and time may have been well spent with interventions such as fluids and vasopressors.…”
mentioning
confidence: 92%
“…For trauma victims, studies have shown that time by minute for treatment is associated with the outcome [6][7][8][9][10]. Several factors account for on-scene time among trauma patients [11][12][13]; however, the actual impact of these factors has not…”
Section: Introductionmentioning
confidence: 99%